2015
DOI: 10.1098/rstb.2014.0292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the within-host fitness effects of mutations fixed during virus adaptation to different ecotypes of a new host

Abstract: One contribution of 17 to a theme issue 'Within-host dynamics of infection: from ecological insights to evolutionary predictions'. The existence of genetic variation for resistance in host populations is assumed to be essential to the spread of an emerging virus. Models predict that the rate of spread slows down with the increasing frequency and higher diversity of resistance alleles in the host population. We have been using the experimental pathosystem Arabidopsis thaliana-tobacco etch potyvirus (TEV) to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
0
21
0
1
Order By: Relevance
“…Some readers may consider the following to be caveats of this study: (i) A. thaliana is not a natural host of TEV, and (ii) all our experiments were performed under controlled greenhouse conditions that may be optimal for virus replication and accumulation. We do not consider the first to be a real problem, as this study, and all previous ones performed with the same experimental pathosystem (25,26,30,(55)(56)(57)(58)(59), deal with the evolutionary determinants and consequences of viral emergence and adaptation to a fully novel host. The second may certainly be an issue to be considered.…”
Section: Figmentioning
confidence: 99%
“…Some readers may consider the following to be caveats of this study: (i) A. thaliana is not a natural host of TEV, and (ii) all our experiments were performed under controlled greenhouse conditions that may be optimal for virus replication and accumulation. We do not consider the first to be a real problem, as this study, and all previous ones performed with the same experimental pathosystem (25,26,30,(55)(56)(57)(58)(59), deal with the evolutionary determinants and consequences of viral emergence and adaptation to a fully novel host. The second may certainly be an issue to be considered.…”
Section: Figmentioning
confidence: 99%
“…The severity of symptoms induced varies widely between species and even between varieties of the same species: from vein clearing, mottling, necrotic etching and plant stunting to less severe symptoms. In a series of evolution experiments [5][6][7][8][9][10][11], we have explored the ability of TEV to expand its host range to a new species that is completely outside its natural host range, the brassica Arabidopsis thaliana ecotype Ler-0. Brassicaceae belong to a different order than Solanaceae within the class Magnoliopsida, hence, adaptation of TEV to A. thaliana represents a jump in host species at the taxonomic level of orders.…”
Section: Experimental Emergence Of a New Rna Virusmentioning
confidence: 99%
“…The perception that synonymous change equates to ‘silent’ change is false [9, 10, 12, 40]. In this report, we add to observations that synonymous substitutions occurring amongst related viral variants may hold answers with respect to viral fitness and evolutionary strategies [9, 14, 41].…”
Section: Discussionmentioning
confidence: 74%
“…HIV-1 treatment resistance mutations have been observed to occur in tandem with subsequent compensatory mutations to correct for consequential loss of fitness [11]. A number of studies have indicated that significant fitness effects can result solely as a consequence of synonymous mutation [10, 1214]. …”
Section: Introductionmentioning
confidence: 99%